Risk of Unexpected Adverse Effects Resulting from the Use of a Skin Test with Recombinant Tuberculosis Allergen in Children - V. N. Kryvohizh; A. M. Korolyuk (LLC "Diagnostics and Vaccines", 2016)
This report reviews clinical cases, and their possible causes of unexpected local and systemic adverse effects associated with a novel skin test using recombinant tuberculosis allergen (RTA, Diaskintest) in 2-11 years old children. This preparation consists of a M. tuberculosis ESAT6/CFP10 fusion protein produced in E. coli, and, in Russia, it has been used as a tool for preventive screening for tuberculosis since 2009. The most common side effects developed within 1 to 12 h after injection and were represented as local or non-life threatening systemic symptoms: fever up to 39°C lasting up to 24 h, painful excessive edema with reddening on the forearm, and, sometimes herpes-like blisters on the skin. In 72 h, the papula at the injection site was moderate, but the hyperemia around it was considerable. We argue that the most likely reason for this type of response could be the development of Type III hypersensitivity (associated with immune complexes), and/or antibody-independent anaphylactoid response to the ESAT6/CFP10 protein or contaminating bacterial culture components. To prevent possible side effects, we recommend to observe the patients for not less than 15 min after the injection of RTA, and to be ready to respond in case of anaphylaxis development.